Sosialisasi Pemanfaatan Limbah Eceng Gondok untuk Bernilai Ekonomis bagi Masyarakat Danau Toba: Socialization of Water Hyacinth Waste Utilization for Economic Value for the Lake Toba Community - Herna Febrianty Sianipar; Rindu Erwin Marpaung; Meliana Gultom; Bernard Simanjuntak; Yosua Marasi Parningotan Siagian; Basar Lolo Siahaan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service project aims to address the serious environmental threat to Lake Toba caused by the massive proliferation of water hyacinth (Eichhornia crassipes), while also offering an economic solution for the surrounding community by utilizing it as a fermented probiotic feed with high monetary value. Lake Toba, as a Super Priority Tourism Destination, requires an integrated waste management solution. The implementation method for this activity involves participatory socialization and live demonstrations, with 50 participants from fish farmers, entrepreneurs, and housewives in the Sibola Hotasas Village area, Balige, North Sumatra Province. The main material presented included identifying water hyacinth nutrients and simple probiotic feed production techniques using probiotic bacteria and molasses. The questionnaire evaluation results showed a significant increase in participants' knowledge, with the average understanding score rising from 45% to 90%, indicating successful technology transfer. The use of water hyacinth as probiotic feed not only contributes to efforts to mitigate ecological waste in Lake Toba waters but also provides a direct economic impact through potential savings in animal feed costs compared to commercial feed. It is hoped that this activity will be the first step toward establishing a communal business unit based on water hyacinth recycling, serving as a model of environmental and economic sustainability for the Lake Toba community.